(untitled) (Medical Forum Monthly, 2021)
Objective: The objective of this study to evaluate Vitamin D deficiency in pregnant women as compare to non –pregnant women. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology KMU-IMS Kohat and Biochemistry of Northwest School of Medicine Peshawar from February, 2018 to August, 2019. Materials and Methods: We include 200 women in this study in which 100 pregnant women and 100 non-pregnant women as control. Blood samples were collected both groups women and centrifuged at 3000 RPM for 10 min for serum. 25(OH) D was estimated from blood serum of the both groups by automatic chemical Analyzer and for estimation used Merk kits. Results: Result of both groups pregnant women and non-pregnant women showed that blood serum 25(OH)D of pregnant women is lower as compare to non-pregnant women. In pregnant women we found 16.1 ng/mL serum vitamin as compare to non-pregnant women in which vitamin D value was 20 ng/mL. Conclusion: The present study demonstrated that in pregnant women high risk of vitamin D deficiency present as compare to non-pregnant women. It is essential that to evaluate vitamin D deficiency in pregnancy and provide vitamin D supplement at early stage.